STRATEGI RETAIL MIX UNTUK MENINGKATKAN DAYA SAING PERITEL DI PASAR TRADISIONAL - Saputra, Murry Harmawan; Ariningsih, Endah Pri (Optimum: Jurnal Ekonomi dan Pembangunan, 2014)
The background of this research is importance of thinking to improve the ability to compete for retailer in traditional markets, in order to able to be a top choice for the consumers. This research aimed to examine and analyze the impact of the retail mix strategy which consists of location, product, price, promotion, service, and store atmosphere on consumer purchase decisions in the traditional markets in the region Kebumen, Central Java. This is a quantitative research with survey method. The subjects were consumers in the region Kebumen traditional markets. The sample used in this study were 210 respondents, sampling methods using purposive sampling technique. Data analysis was performed using multiple regression analysis techniques to process the data in order to produce information in accordance with the purpose of research. The results of this study indicate that all the hypotheses are supported. All variables retail mix positive infl uence and signifi cant on consumer purchase decisions.